Love you, mean it : a novel - Gagnon, Jilly (Bantam Dell, 2024)
"Ellie Greco is not happy to be stuck in Milborough. For a few brief, shining years, she managed to get away from her hometown to pursue her dream career--designing beautiful, elaborate costumes for theater--until her father's death five years ago called her home to run the family's decades-old deli. Now, out of loyalty to him she keeps it running, trying to bring it into the twenty-first century with trendy ingredients like truffle oils and tinned fish, all the while wondering if she'll ever get another chance at a life on her terms. But when Ellie hears that a local landlord is planning to rent to Mangia, the big-chain purveyor of gourmet foods, Greco's Deli's very existence is suddenly in jeopardy. And it's up to Ellie to save it. She tries to plead her case to Theo Taylor, who works for his father at the property management firm about to put her out of business, but their meeting goes disastrously. Ellie finds Theo arrogant and money-hungry; Theo thinks Ellie is rude and hot-headed. To say they start off on the wrong foot . . . is an understatement. But when an accident in the middle of their meeting sends Theo to the hospital, unconscious, Ellie panics and claims to be his doting fiancée. When he comes to, he's surprised to find himself engaged--until he realizes Ellie's plan to save her deli is the key to helping him get out from under his overbearing father's thumb and decides to play along. The pretend engagement is a perfect plan - if they can play nice for long enough to convince Theo Taylor, Sr. But the more time they spend scheming together, the more they realize there might be a genuine connection between them."--